Mechanical, Cardiorespiratory, and Muscular Oxygenation Responses to Sprint Interval Exercises Under Different Hypoxic Conditions in Healthy Moderately Trained Men - Solsona, Robert; Berthelot, Hugues; Borrani, Fabio; Sanchez, Anthony M. J. (Frontiers in Physiology, 2021)
Objective: The aim of this study was to determine the effects of sprint interval exercises (SIT) conducted under different conditions (hypoxia and blood flow restriction [BFR]) on mechanical, cardiorespiratory, and muscular O2 extraction responses. Methods: For this purpose, 13 healthy moderately trained men completed five bouts of 30 s all-out exercises interspaced by 4 min resting periods with lower limb bilateral BFR at 60% of the femoral artery occlusive pressure (BFR60) during the first 2 min of recovery, with gravity-induced BFR (pedaling in supine position; G-BFR), in a hypoxic chamber (FiO2≈13%; HYP) or without additional stress (NOR). Peak and average power, time to achieve peak power, rating of perceived exertion (RPE), and a fatigue index (FI) were analyzed. Gas exchanges and muscular oxygenation were measured by metabolic cart and NIRS, respectively. Heart rate (HR) and peripheral oxygen saturation (SpO2) were continuously recorded. Results: Regarding mechanical responses, peak and average power decreased after each sprint (p < 0.001) excepting between sprints four and five. Time to reach peak power increased between the three first sprints and sprint number five (p < 0.001). RPE increased throughout the exercises (p < 0.001). Of note, peak and average power, time to achieve peak power and RPE were lower in G-BFR (p < 0.001). Results also showed that SpO2 decreased in the last sprints for all the conditions and was lower for HYP (p < 0.001). In addition, Δ[O2Hb] increased in the last two sprints (p < 0.001). Concerning cardiorespiratory parameters, BFR60 application induced a decrease in gas exchange rates, which increased after its release compared to the other conditions (p < 0.001). Moreover, muscle blood concentration was higher for BFR60 (p < 0.001). Importantly, average and peak oxygen consumption and muscular oxyhemoglobin availability during sprints decreased for HYP (p < 0.001). Finally, the tissue saturation index was lower in G-BFR. Conclusions: Thus, SIT associated with G-BFR displayed lower mechanical, cardiorespiratory responses, and skeletal muscle oxygenation than the other conditions. Exercise with BFR60 promotes higher blood accumulation within working muscles, suggesting that BFR60 may additionally affect cellular stress. In addition, HYP and G-BFR induced local hypoxia with higher levels for G-BFR when considering both exercise bouts and recovery periods.